The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1152/ajprenal.00150.2016
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase inhibition increases AQP2 accumulation in the rat IMCD apical plasma membrane

Abstract: Vasopressin triggers the phosphorylation and apical plasma membrane accumulation of aquaporin 2 (AQP2), and it plays an essential role in urine concentration. Vasopressin, acting through protein kinase A, phosphorylates AQP2. However, the phosphorylation state of AQP2 could also be affected by the action of protein phosphatases (PPs). Rat inner medullas (IM) were incubated with calyculin (PP1 and PP2A inhibitor, 50 nM) or tacrolimus (PP2B inhibitor, 100 nM). Calyculin did not affect total AQP2 protein abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…AQP2 is one of the most important channel proteins involved in regulating urine concentration, and is located at the apical membrane of principal cells in the collecting duct [14]. The water reabsorption function of AQP2 is mainly regulated by arginine vasopressin (AVP) via increasing intracellular production of cyclic adenosine monophosphatase (cAMP) and further phosphorylation of AQP2 at Ser256 and Ser269 to stimulate the intracellular trafficking of AQP2 to the plasma membrane [15,16,17] (Figure 2). Besides AVP, researchers have demonstrated that activation of bile acid receptor TGR5 and hydrogen sulfide (H 2 S) stimulates the expression of AQP2 via cAMP-protein kinase A (PKA) signaling pathway and attenuates the defection of urinary concentration in mice [18,19].…”
Section: Expression Of Physiological Function Of Aqps In the Kidneymentioning
confidence: 99%
“…AQP2 is one of the most important channel proteins involved in regulating urine concentration, and is located at the apical membrane of principal cells in the collecting duct [14]. The water reabsorption function of AQP2 is mainly regulated by arginine vasopressin (AVP) via increasing intracellular production of cyclic adenosine monophosphatase (cAMP) and further phosphorylation of AQP2 at Ser256 and Ser269 to stimulate the intracellular trafficking of AQP2 to the plasma membrane [15,16,17] (Figure 2). Besides AVP, researchers have demonstrated that activation of bile acid receptor TGR5 and hydrogen sulfide (H 2 S) stimulates the expression of AQP2 via cAMP-protein kinase A (PKA) signaling pathway and attenuates the defection of urinary concentration in mice [18,19].…”
Section: Expression Of Physiological Function Of Aqps In the Kidneymentioning
confidence: 99%
“…In addition to the involvement of PP2A in AQP2 regulation, protein phosphatase 2B (PP2B), one of components of AKAPs-containing multiple complex has also been proposed to dephosphorylate endosome-bounded AQP2 (44). A recent study demonstrated that multiple phosphatases are involved in the subcellular localization of phosphorylated AQP2, and particularly PP1/PP2A plays a role in the AQP2 phosphorylation and AQP2 expression in the apical plasma membrane (116). Comprehensive understanding of the effects of multiple kinases under different conditions, such as activity and specificity against each phosphorylation site of AQP2 and the interaction with other proteins, could provide information for better understanding of the phosphorylationmediated AQP2 trafficking.…”
Section: Role Of Phosphatidylinositol-3-kinase/akt Gsk3 and Cyclin-mentioning
confidence: 99%
“…Aldosterone increases calcineurin activity in rat cortical collecting ducts through an MR-dependent but transcription-independent mechanism [11]. Our published data show that inhibiting calcineurin alters the phosphorylation and the activity of the urea transporter UT-A1 in the IMCD [12,13].…”
Section: Introductionmentioning
confidence: 84%
“…Previous studies show aldosterone increases urine production and decreases apical AQP2 expression in rats with diabetes insipidus, suggesting that aldosterone may decrease vasopressinstimulated osmotic water permeability [13,22]. There are some sex-specific differences in blood pressure control and water homeostasis (reviewed in [29]).…”
Section: Discussionmentioning
confidence: 99%